Electronic Governance: Issues and Challenges in India and the future (International Journal of Food and Nutritional Sciences, 2022)
Electronic governance, commonly known as “e-governance”, refers to the use of technology and digital tools to improve the efficiency, transparency, and effectiveness of government services and processes. In India, “e-governance” has been an important policy objective for several years, with the aim of enhancing citizen participation and reducing corruption. However, the implementation of “e-governance” has been met with several challenges and issues that hinder its success.